The role of endothelial cells in pancreatic islet development, transplantation and culture - Geng, Ajun; Yuan, Shubo; Yu, Qing Cissy; Zeng, Yi Arial (Frontiers in Cell and Developmental Biology, 2025)
Endothelial cells (ECs) play pivotal roles in the development and maintenance of tissue homeostasis. During development, vasculature actively involves in organ morphogenesis and functional maturation, through the secretion of angiocrine factors and extracellular matrix components. Islets of Langerhans, essential functional units of glucose homeostasis, are embedded in a dense endothelial capillary network. Islet vasculature not only supplies nutrients and oxygen to endocrine cells but also facilitate the rapid delivery of pancreatic hormones to target tissues, thereby ensuring precise glucose regulation. Diabetes mellitus is a major disease burden and is caused by islet dysfunction or depletion, often accompanied by vessel loss and dysregulation. Therefore, elucidating the regulatory mechanisms of ECs within islets hold profound implications for diabetes therapy. This review provides an overview of recent research advancements on the functional roles of ECs in islet biology, transplantation, and in vitro islet organoid culture.